PELATIHAN PENGURUSAN JENAZAH SEBAGAI UPAYA PENINGKATAN PEMAHAMAN DAN KETERAMPILAN MASYARAKAT DESA PETUNG - Pasmadi, Achmad Kurniawan; Rahmawati, Vivin; Fitanisa, Faya (Jurusan Pendidikan Bahasa dan Seni, FKIP Universitas Lampung, 2025)
This journal describes a community service program (PKL) aimed at providing an in-depth explanation and understanding of the practice of venerating the dead in accordance with Islamic law to the Muslim community of Petung Village. We engaged experienced speakers in funeral arrangements, and involved Petung Village Community Service Program (KKN) participants as intermediaries between the Petung Village community and the speakers. The participants also participated in the funeral arrangements themselves. During the funeral training, the speakers explained and demonstrated the procedures for venerating the dead in accordance with religious teachings, incorporating elements of invitation as part of both oral and written da'wah (propaganda). The funeral training included distributing shrouds, bathing, shrouding, and praying over the body. By providing education, understanding, and training to the Petung Village community, we hope to enhance their understanding and develop skills that can be used in situations involving funeral arrangements in Petung Village. Apart from providing benefits to the community, this service activity also provides benefits for students participating in KKN in Petung Village, and can be applied in life when in the community and students have skills in venerating corpses and gain very valuable learning experiences. Jurnal ini menggambarkan pengabdian kuliah kerja nyata yang bertujuan untuk memberikan penjelasan dan memamahami secara mendalam praktik pemuliaan jenazah sesuai dengan syari’at agama Islam kepada masyarakat Desa Petung yang beragama Islam. Kami melibatkan pemateri yang benar benar sudah berpengalaman dalam kepengurusan jenazah dan melibatkan peserta KKN Desa Petung sebagai perantara antara masyarakat Desa Petung dan pemateri, serta peserta KKN ikut andil dalam praktik kepengurusan jenazah. Selama proses pelatihan pengurusan jenazah pemateri menjelaskan dan mempraktikkan mengenai tata cara pemuliaan jenazah sesuai ajaran agama serta memasukkan unsur-unsur ajakan sebagai dakwah bil lisan dan bil hal. Praktik pelatihan jenazah meliputi membagi kain kafan, memandikan, mengkafani, serta mensholatkan jenazah. Dengan memberikan pengajaran, pemahaman dan pelatihan kepada masyarakat Desa Petung kami berharap agar masyarakat Desa Petung lebih paham serta mengembangkan ketrampilan masyarakat yang dapat digunakan dalam situasi ketika menghadapi pengurusan jenazah di Desa Petung. Selain memberikan manfaat kepada masyarakat kegatan pengabdian ini juga memberikan manfaat bagi mahasiswa peserta KKN di Desa Petung, dan bisa diterapkan dalam kehidupan ketika bermasyarakat serta mahasiswa memiliki ketrampilan dalam memuliakan jenazah dan memperoleh pengalaman belajar yang sangat berharga.